Consumo, digestibilidade e balanço de nitrogênio de cordeiros alimentados com alto teor de amido ou fibra solúvel em detergente neutro associados ao óleo de girassol - Morgado, Eliane da Silva [UNESP] (2014)
The aim of this study was to evaluate the effect of different carbohydrate sources associated with sunflower oil on intake, digestibility of nutrients and nitrogen balance in diets of lambs. Twenty lambs were used, assigned in a completely randomized design with a 2 x 2 factorial arrangement of treatments with two sources of neutral detergent soluble carbohydrate, starch and neutral detergent soluble fiber, with and without the inclusion of 4.2% sunflower oil. The dry matter intake was not affected by carbohydrate sources and the inclusion of oil. Diets with a high percentage of starch provided higher digestibility of dry matter, starch and ether extract. The different sources of carbohydrates had no interference on digestibility of organic matter, crude protein, neutral detergent soluble fiber, nonfiber carbohydrates, neutral detergent fiber, hemicellulose and acid detergent fiber. The addition of oil in the diets increased the digestibility of ether extract. The combination of 4.2% oil in the diet high in soluble neutral detergent fiber had no influence on the nutrient digestibility, otherwise, the addition of oil at high starch diet caused a significant reduction in the digestibility of organic matter, neutral detergent fiber, hemicellulose and nonfiber carbohydrates. The quantities of nitrogen intake, absorbed and retained, did not differ as sources of carbohydrates and oil inclusion in the diet. The association of 4.2 % sunflower oil to the different sources of carbohydrates in the diet does not affect consumption and nitrogen metabolism in lambs. The addition of 4.2 % oil in the diet with high starch (28% of DM diet) promotes reduction in digestibility of organic matter, of fibrous and nonfibrous carbohydrate in the diet.